2020
DOI: 10.1097/bpb.0000000000000835
|View full text |Cite
|
Sign up to set email alerts
|

Do the clinical scores (Pirani and Dimeglio scores) correlate with the radiological parameters in idiopathic club foot in infants? A cross-sectional study

Abstract: This study was done to identify how well clinical scores and their sub-scores correlate with the radiographic parameters in idiopathic clubfoot. We studied 76 patients of idiopathic clubfoot who are from 5 months to 12 months of age. Deformity was assessed clinically with Pirani and Dimeglio scores and radiologically using eight parameters. Correlation between clinical and radiological scores was studied. All the eight radiological parameters were showing statistically significant correlation with clinical sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We suggest that early identification of residual clubfeet can be carried out with a carefully performed Pirani score at three months or a lateral radiograph in maximum dorsiflexion at three months, along with measurement of the talocalcaneal and tibiocalcaneal angle. Sriharsha found high correlations between radiographs and the Pirani score [ 26 ]. The limited numbers included in this study do not allow us to prove that the Pirani score is better than the radiograph at predicting additional surgery, but the multivariate data indeed suggest it; moreover, radiation could be spared.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that early identification of residual clubfeet can be carried out with a carefully performed Pirani score at three months or a lateral radiograph in maximum dorsiflexion at three months, along with measurement of the talocalcaneal and tibiocalcaneal angle. Sriharsha found high correlations between radiographs and the Pirani score [ 26 ]. The limited numbers included in this study do not allow us to prove that the Pirani score is better than the radiograph at predicting additional surgery, but the multivariate data indeed suggest it; moreover, radiation could be spared.…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any wound or plaster-related complications in any of the feet. Studies have shown that the initial Pirani score correlates with radiological parameters but is not necessarily correlated to the final outcome in terms of the number of casts required for correction [28,29]. At the final follow-up, all the feet had become plantigrade with a Pirani score of zero, and there were no recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, some authors reported the involvement of lower limbs genetic mechanisms and possible influence on the development of tarsal bones [5]. Radiographic and sonographic studies on the development of tarsal bone shape in treated clubfeet revealed marked differences from normal feet but observed also some methodological difficulty in detecting morphological differences with these imaging modalities [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%